Sweet & sound utilizing illustrative narrative to ease transition to bedtime for children - Ong, Han Yu (2015)
Sweet & Sound is a design initiative aimed at promoting sleep hygiene in Pre-school children (2-4 years old). The project examined how illustrative design can facilitate transition to bedtime for children. The project focused on utilizing illustrative narration and local imagery to enhance environmental and lifestyle factors to promote good sleep hygiene, thereby assisting children to transit to bedtime. By developing good sleep hygiene at a young age, the project sought to minimize sleep problems in children to promote good mental health and well-being